REVIEW OF PHARMACOEPIGENETICS: BRIDGING EPIGENETICS AND PERSONALIZED MEDICINE - Harshika. D. Kulkarni; Yogesh. B. Rokade; Akash Jain; Dr. Sunil. P. Pawar; Vidhya Jagdale; Chetana Jain (International Journal of Molecular Biotechnological Research, 2026)
Pharmacoepigenetics is an emerging field that explores how alterations in gene expression, independent of DNA sequence changes, influence individual responses to drugs. Unlike pharmacogenetics, which focuses primarily on genetic variation, pharmacoepigenetics integrates genetic, environmental, and lifestyle factors to explain interindividual differences in drug efficacy, toxicity, and resistance. Key epigenetic mechanisms including DNA methylation, histone modifications, non-coding RNAs, and RNA methylation play critical roles in regulating drug metabolism and therapeutic outcomes. This review highlights the growing clinical relevance of pharmacoepigenetics in cancer, neurological, and cardiovascular disorders, where epigenetic biomarkers and targeted therapeutics are reshaping treatment strategies. Epigenetic agents such as DNMT, HDAC, and EZH2 inhibitors can restore normal gene expression and enhance drug sensitivity. Despite these advances, challenges remain in biomarker validation, data interpretation, and establishing causal links between epigenetic modifications and treatment response. Integration of CRISPR-based epigenome editing, artificial intelligence, and multi-omics approaches is anticipated to accelerate the clinical translation of pharmacoepigenetic insights, enabling safer, more effective, and truly personalized therapies.
Keywords: DNA Methylation; Epigenetics biomarkers; Non-coding RNA; Personalized medicine; Pharmacoepigenetics